Comparison of The Effects of General and Spinal on Apgar Scores of Babies Born Through Caesarean Section in RSUP Haji Adam Malik Medan from 2018 to 2019 - Rambe, Aldo Putra; Nasution, Akhyar Hamonangan; Cut Meliza Zainumi; Nova Zairina Lubis (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background.Â General anesthesia and spinal anesthesia in cesarean section both have advantages and disadvantages. The scoring system of APGAR is a standardized tool that can inform the condition of newborn infants, which might be influenced by gestational age, medication, resuscitation, cardiorespiratory and neurological conditions of the mother. This study aimed to compare the effect of general and spinal anesthesia usage to the APGAR score of newborn infants at Haji Adam Malik General Hospital Medan. Methode. This study uses an observational-analytic design with a cross-sectional approach,Â conducted using secondary data through the medical records of mothers who gave birth through cesarean section and obtained at the Medical Record Installation at the Haji Adam Malik Hospital Medan from 2018 to 2019. Result. In spinal anesthesia, there are 52 samples for a score of 8-10. Whereas in general anesthesia, there are 52 samples to score 8-10. The APGAR score of 1 minute in infants born through cesarean section under spinal anesthesia had an average of 8.63, with general anesthesia of 8.00 (p=0.001). The 5-minute APGAR score in infants born through cesarean section under spinal anesthesia had an average of 9.85, and with general anesthesia of 8.67 (p=1.000). Conclusion: The 1-minute APGAR score for infants using spinal anesthesia showed a statistically better effect than the 1-minute APGAR score for infants using general anesthesia.